Evaluating The Leadership Competencies and Practices of School Heads in Implementing the School-Based Management - Mylah N. Guerrero (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study examined the relationship between school heads’ leadership competencies and the implementation of School-Based Management (SBM) practices in public schools in the Municipality of Aroroy. Employing a descriptive-correlational research design, data were collected from the 44 accessible school heads using a structured questionnaire aligned with the Philippine Professional Standards for School Heads (PPSSH) and SBM indicators under DepEd Order No. 7, s. 2024. Descriptive statistics and Pearson Product-Moment Correlation were utilized for data analysis.  Results indicated that school heads demonstrated very high competency across key leadership domains, including strategic leadership, resource management, instructional leadership, and stakeholder engagement. SBM practices were likewise found to be highly to very highly manifested, particularly in the domains of learning environment, governance, and curriculum implementation. Further analysis revealed a statistically significant and very strong positive correlation (r = 0.87, p < .05) between leadership competencies and SBM implementation, suggesting that higher levels of leadership proficiency are associated with more effective and consistent SBM practices. These findings highlight the centrality of leadership capacity in advancing decentralized school governance and improving educational outcomes. The study underscores the need for sustained, competency-based leadership development interventions, including structured mentoring, coaching systems, and instructional leadership enhancement programs. Strengthening leadership competencies aligned with PPSSH is therefore essential for optimizing SBM implementation and ensuring continuous school improvement in diverse and resource-constrained educational settings.